2005
DOI: 10.1080/08035250510032646
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin-induced cell death during continuous and intermittent phototherapy and in the dark

Abstract: Continuous and intermittent light exposure caused the same degree of apoptotic cell death, while the cells underwent more necrotic death after intermittent exposure. Bilirubin was cytotoxic in the dark by both cell death mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is generally believed that bilirubin photoisomers are non-toxic; however, no clear evidence for this viewpoint exists, and insufficient data about bilirubin PI's biological effects have thus far been provided. [ 16 23 ]. Of note is the fact that in none of these studies were the pure forms of the bilirubin photoderivatives used, most likely because of their complicated isolation and handling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally believed that bilirubin photoisomers are non-toxic; however, no clear evidence for this viewpoint exists, and insufficient data about bilirubin PI's biological effects have thus far been provided. [ 16 23 ]. Of note is the fact that in none of these studies were the pure forms of the bilirubin photoderivatives used, most likely because of their complicated isolation and handling.…”
Section: Discussionmentioning
confidence: 99%
“…Nothing is known about whether bilirubin PI may affect the bilirubin-albumin interaction. Previous studies on the biological effects of bilirubin photoproducts [ 16 23 ] suffered from a major limitation (insufficient purity of the bilirubin photoproducts), as well as inconsistent study designs. Thus, there is still uncertainty on the potential toxicity of bilirubin breakdown products not only for the central nervous system, but also other organs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the proportion of the apoptotic cells in the epithelium of the small intestine was 1.7% in the control group, and grew to 3.1 and 6.2% in the LED group and the conventional group, respectively. Phototherapy increases apoptosis due to cell damage depending on wavelength [11,12]. The two lamps, a turquoise (green) fluorescent phototherapy lamp (490 nm) and a conventional blue phototherapy lamp (450 nm), were similar in the formation of therapeutically relevant photoproducts, but the blue lamp showed potential in forming more severe cellular damage by the difference of wavelength [12].…”
Section: Discussionmentioning
confidence: 99%
“…Roll and Christensen measured apoptotic or necrotic cells induced by phototherapy using a mouse lymphoma cell line, and concluded that the emitted light increased apoptosis and necrosis due to photo-oxidation and cell damage in vitro [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation